Perancangan Decision Support System Berbasis Website Untuk Pengawasan Risiko Pada Institusi Pengawas Tenaga Nuklir - Muluk, Asmuliardi; Yulianto, Ardhian Agung; Ananda, Billy Fadilah (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Safety risk surveillance at nuclear facilities is an important element in ensuring the protection of workers, the public, and the environment from radiation hazards. The Nuclear Power Supervisory Institution manages large data related to nuclear safety risk surveillance. However, this very large and diverse volume of data causes difficulties in adequate processing and analysis, thus hampering the speed and accuracy of supervisory decision making. The main obstacle faced is data management that is still manual and less integrated so that the risk monitoring process becomes less efficient. Therefore, this research designs a website-based Decision Support System (DSS) with the Analytic Hierarchy Process (AHP) method to assist the decision-making process that is more objective, accurate, and based on risk priorities in nuclear safety. The results showed that the use of the AHP method in DSS was able to provide priority weights for risk criteria in an objective and structured manner. Consistency Ratio (CR) of 0.0066 shows a good level of assessment consistency. This system facilitates data visualization and presents safety risk inspection priority recommendations effectively through an interactive dashboard. The designed DSS is expected to improve the efficiency and effectiveness of nuclear safety risk monitoring at the Nuclear Power Supervisory Institution.